Religion and the Secular: Two Very Different Perspectives That Find Them Difficult to Distinguish - Rennie, Bryan S. (Implicit religion, 2013)
The article reviews the book "The Discipline of Religion: Structure, Meaning, Rhetoric" by Russell T. McCutcheon.